Design and research of adaptive O-OFDM symbol decomposing with serial transmission system in visible light communication - Kejun JIA; Boran YANG; Minghua CAO; Suoping LI; Li HAO (Tongxin xuebao)
Iterative signal clipping (ISC) and symbol decomposing with serial transmission (SDST) techniques decompose optical orthogonal frequency division multiplexing (O-OFDM) symbol into the fixed number of multiple small-amplitude symbols.However,at low O-OFDM symbol variances,the decomposition symbols contain a large amount of all-zero symbols without load information,which results in bit error rate degradation,optical power penalty and information rate reduction.Aim at this problem,an adaptive O-OFDM symbol decomposing with serial transmission (ASDST) system was proposed,the symbol decomposition was adaptively determined according to the O-OFDM symbol amplitude.Symbol decomposition was terminated until O-OFDM symbol was completely decomposed or the maximum symbol decomposition times were attained,thereby eliminated all-zero symbols and reduced the average symbol decomposition times.The performance of ASDST system was verified by theoretical analysis and Monte Carlo simulation.